School Governance and Academic Excellence: The Representations of Distinguished Students in an Annual Award of Excellence - José Augusto Palhares; Leonor Lima Torres (LED Edizioni Universitarie, 2015)
Within a research project on «academic excellence in the state school», this paper is a contribution to the sociological reflection on the cultural and organisational characteristics of the school and its relationship with the academic success of students. The data we present stem from a case study underway at a secondary school in the north of Portugal, referring to the universe of students that since 2003 have distinguished themselves for achieving grades equal to or greater than 18 (on a scale of 0 to 20) and have thus been included in the school's Framework of Excellence. From a contextual approach to this educational practice, we focused on the cultural characteristics of the school/subject as analytical support for the study of school and non-school dimensions in their mutual connections. To this end, we used the information from document analysis and data collected from a questionnaire survey administered to more than two-thirds of the students included in the above-mentioned Framework of Excellence. Subsequently, we will use the data from this survey to understand the extent to which academic excellence is perceived as an indivisible social construction of the school's political and organisational matrix, particularly in terms of the educational and teaching guidelines adopted by the management body. We will conclude by questioning the meaning of the school's management policies regarding the emphasis on educational outcomes, with particular focus on the representations of excellent students in the processes of school leadership, teaching organisation, school merit and justice.